Politics, Governance, and Leadership: What Can We Learn From the Academy of Management's Response to EO13769?. (July 2019) - Davis, Gerald F.; Anteby, Michel; Briscoe, Forrest S.; Jennings, P. Devereaux; Karim, Samina; Kaul, Aseem; Lazzarini, Sergio; Özkazanç-Pan, Banu; Donnelly, Paul; Rasche, Andreas; Tsui, Anne S.; Wright, Thomas A.; et al.
Organization design seeks to balance potentially conflicting objectives while achieving a broader mission. EO13769 created a challenge for the president of the Academy of Management in leading through these conflicts, as President Anita McGahan describes: how to be true to her own moral values while leading an organization with well-established design constraints, and members with diverse opinions. This article shares the perspectives of 12 scholars on the lessons we can learn from Professor McGahan's leadership of a constraining organization through a challenging time.